Pengembangan Modul Kewirausahaan Berbasis Project-Based Learning pada Program Studi Manajemen Pendidikan Islam - Dian Pratiwi (Southeast Asian Journal of Islamic Education Management, 2025)
The urgency of this research arises from the limited availability of teaching resources that effectively integrate entrepreneurship theory with practical experience, resulting in students’ difficulties in fully developing an entrepreneurial mindset. The study adopted a Research and Development (R&D) approach using the 4D model: Define, Design, Develop, and Disseminate. However, due to time and funding constraints, the research was limited to the Develop stage. Validation results from two experts in entrepreneurship and curriculum development indicated a very high level of feasibility, with an average score of 94.1% across aspects of content, structure, readability, and the application of PjBL principles. The module is considered valid, practical, and ready for classroom use. Its strengths lie in integrating entrepreneurial theory and practice, emphasizing active and collaborative learning, and embedding Islamic values in project activities. This study is expected to contribute significantly to the development of innovative entrepreneurship pedagogy in Islamic higher education, while also strengthening students’ competencies in critical thinking, communication, collaboration, innovation, and decision-making. Further research is recommended to examine the module’s effectiveness across broader classroom contexts and diverse learning settings.